Analisis dan Perancangan Antar Muka sebagai bentuk Visualisasi Rancang Bangun Sistem Aplikasi Pengiriman Barang berbasis Website pada CV Rizky Agung - Sari, Gita Puspita; Rahmawati, Endra; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
CV Rizky Agung is a company engaged in the delivery of goods in the city of Surabaya by sea. Currently, the process at CV Rizky Agung has several processes, namely the delivery transaction process, transaction data recording, and the delivery of goods. In these processes assisted with the help of Microsoft Excel to record all the data. The problem that occurs in the company is that customers cannot find out information about goods in real time, quickly whether the goods have been sent or not. In the current conditions, the application of restrictions on offline transactions during the Covid-19 pandemic, all transactional transactions were transferred to the online system, thus encouraging the company to create a website-based goods delivery system. With complaints from customers when they have difficulty monitoring goods, these needs will be met through "Interface Analysis and Design as a form of Visualization of Website-based Goods Delivery Application System Design at CV Rizky Agung". The final results obtained are in the form of Interface Design and Analysis as a form of Visualization of the Website-based Goods Delivery Application System Design on CV Rizky Agung in order to know for sure the main needs of users, especially during the Covid-19 pandemic. The survey filled by respondents in this study amounted to 21 people with details of 2 couriers, 2 admins, and 17 customers. Based on the value of the survey, it will be calculated using the System Usability Scale formula which gets an average value of 80.5, which means that usability based on the data gets an acceptable or feasible assessment.